TELAAH DINAMIKA ORBIT ASTEROID ATIRA - Saputra Hutasoit, Adi
The study of the dynamics of asteroid orbits is still being studied, and in this study, the asteroid Atira, which is one of the near-Earth asteroid groups (ADB) is our concern. Asteroid Atira is defined as an asteroid with an Q < 0.983 au and a < 1.0 au. Our analysis of the dynamics of the orbit of the asteroid Atira is based on classical mechanics, involving the Sun as the central star, 8 interfering planets, namely Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus, Neptune and 27 asteroid Atira, at the epoch January 21, 2022 and downloaded on January 03, 2022. The input data is downloaded from the “HORIZON System” database available on the page https: // ssd. jpl. nasa. gov/ tools/ sbdb_ query. html for the integration process. The integration process uses the IAS15 integrator contained in the REBOUND programming package. Integration is carried out for the next 107 years/2? with a calculation iteration (time step) of 0.01 years. The purpose of this Final Project is to analyze the dynamics of the Atira Asteroid orbit based on the formulation of Classical Mechanics and to analyze the orbital dynamics of the Atira Asteroid by adding Post-newtonian effects to the calculations. From the integration results of the orbit parameters of 27 Atira asteroids for a period of 107 years/2? from the epoch of each asteroid, it was found that some Atira asteroids experienced oscillations using both the Newtonian effect and the Post-newtonian effect. Beside from oscillations, one of Atira’s has a coorbital with the Newtonian case, namely 2004 XZ130 in the time span of 4570000 years/2? until the end of integration. At the end of integration, some of the Atira asteroids undergo group changes with the Newtonian effect and Post-newtonian effect. With the Newtonian effect, there are 7 Atira asteroids that underwent a group change to Aten and 2 Atira asteroids that underwent a group change to Apollo. With the Postnewtonian effect, there are 7 Atira asteroid that underwent a group change to Aten and 3 Atira asteroids that underwent a group change to Apollo, with different Atira asteroids that underwent a group change between Newtonian effect and Post-newtonian effect.